Smoking and alcohol abuse by medical practitioners: an insult to the noble profession - Naveena, T. (International Journal Of Community Medicine And Public Health, 2016)
Smoking and alcohol are the dreadful dangerous factors which not only affect the lives of the culprits but also the innocents. Smoking is the greatest cause of illness and premature death in the world. It is most common cause of oral and lung cancers. It is one of the risk factor for obstructive lung diseases (like emphysema, chronic bronchitis, COPD), heart diseases, brain strokes, infertility in women etc., Alcohol consumption is one of the dangerous habits and causes liver damage, brain damage and heart attack. Though alcohol is said to enhance high density lipoproteins and useful to us in many aspects when consumed in less quantities, it may lead to dependence on consuming daily. Ill effects of alcohol and smoking on human body never end.